PENGARUH TERAPI AKUPUNKTUR TERHADAP PENURUNAN TINGKAT NYERI PASIEN LOW BACK PAIN (LBP) DI POLINEUROLOGI RSUD Dr. HARJONO PONOROGO - Purwanto Purwanto; Henny Purwandari; Moh Ari Arfianto (STRADA : Jurnal Ilmiah Kesehatan, 2012)
Human daily activities demanding motion or bending forRoom than backRoom, strenuous activities such as lifting heavy loads incorrectly, or the sitting position with a long period of time causes pain in the limbs, the arms, the joints and muscle tissue. The purpose of this study to determine the effect of acupuncture on patients’ pain levels decreased Low Back Pain (LBP) in Neurology Room Dr. Harjono Ponorogo Hospital. This type of research pre-experimental research design One-Group Prepost test design. The sample was patient Low Back Pain (LBP) who meet the inclusion and exclusion criteria in Neurology Room Dr. Harjono Ponorogo Hospital months 1 to 31 December 2012 as many as 20 patients with LBP. The analysis used was Wilcoxon signed rank test, with α = (0.05). Results showed before being given acupuncture treatment most severe levels of pain categories were 11 (55%) and the level of pain after acupuncture treatment was given most of the categories were as many as 12 (60%). The results of the analysis obtained by Wilcoxon sign rank test p value (0.000) <α = (0.05) then there is the effect of acupuncture on patients’ pain levels decreased Low Back Pain (LBP) in Neurology Room Dr. Harjono Ponorogo Hospital. Acupuncture therapy effectively reduce the patient’s pain, but keep in mind the factors that affect the level of pain such as gender, age, education, occupation, and length of employment so that the results can be optimal acupuncture therapy.